2001
DOI: 10.1093/molehr/7.7.681
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the normal human amnion at term, independent of Bcl-2 regulation and onset of labour

Abstract: This study was designed to detect apoptosis in the human amnion and to elucidate the signalling pathway involved in its regulation. Samples of human amnion were obtained from 34 women (weeks 11-42 of gestation) and studied using the terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labelling (TUNEL) method with light microscopy (LM) and transmission electron microscopy (TEM). Apoptotic regulators in the samples were studied by immunohistochemistry and caspase activity assay. The TUNEL method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 30 publications
1
21
0
6
Order By: Relevance
“…The first of these networks- cell death, cancer and morphology- is consistent with marked increase in apoptosis observed with the preparation of the amnion for rupture [36], [37] via the delamination and apoptosis of amnion epithelial cells (Figure 6). However, this observation contrasts with the well described role for NFκB as an anti-apoptotic transcription factor [38].…”
Section: Discussionsupporting
confidence: 74%
“…The first of these networks- cell death, cancer and morphology- is consistent with marked increase in apoptosis observed with the preparation of the amnion for rupture [36], [37] via the delamination and apoptosis of amnion epithelial cells (Figure 6). However, this observation contrasts with the well described role for NFκB as an anti-apoptotic transcription factor [38].…”
Section: Discussionsupporting
confidence: 74%
“…In addition, there were no significant differences noted when fetoscopically repaired cases were compared with open repaired cases. Apoptosis is a type of cell death controlled by a series of molecular events and is executed by a family of cysteine‐containing aspartate‐specific proteases called the caspase family . Previous studies on patients who had undergone laser treatment for twin‐twin‐transfusion syndrome (TTTS) using TUNEL staining showed increased cell death .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that the number of apoptotic cells was much higher in the chorion of fetal membranes with histological chorioamnionitis at term than those without chorioamnionitis [92] and that the chorion of fetal membranes from patients with premature rupture of membranes had significantly more apoptotic cells than those without chorioamnionitis [93]. In addition, apoptosis was detected in also amnion epithelial cells at term, which was associated with onset of labor [94]. It is likely that apoptotic cell death in broad area of the fetal membranes is responsible for the rupture of fetal membranes both at term under physiological conditions and at preterm with chorioamnionitis.…”
Section: Production Of Proinflammatory and Chemoattractive Cytokinmentioning
confidence: 99%